A Study on the Effect of Ola/Uber Taxi Services over the Local Taxi Services in Kerala - R. , Anand; B Das, Jyothis; K. , Krupa; P Kurup, Prateek; C.V. , Durgalakshmi (International Journal of Psychosocial Rehabilitation, 2020)
A study was conducted regarding the effect of Ola/Uber taxi services over the local taxi services in Kerala. There are various types of taxi services operating in our state. Among them, traditional taxis and Uber/Ola are common. The public is mostly interested in Uber and Ola services because their services are very convenient and reasonable in cost. Uber taxi drivers are ready to work more hours than traditional taxis. Traditional taxi drivers are mainly operating from their authorized taxi stand, whereas Uber taxis operate from the point where they drop their last customer. Most of the traditional taxi drivers are aware of the route and location where the customer has to go. This is because of their long experience in this field. In today’s modern world, people use Google Maps, in which they get the exact location, name of place, and exact distance. Most of the traditional drivers are not willing to operate at night, as they must reach their home to look after their family. Some of the traditional drivers charge more than the prescribed government rate. This creates a bad impression among the customers.